The Use Of Cyber Notary In The Gms Is Reviewed From Legal Benefit - Liauw, Yantje (PT. Hafasy Dwi Nawasena, 2024)
The use of cyber notary technology in the General Meeting of Shareholders (GMS) is an important highlight in the context of legal expediency. With the provisions of Article 77 of the Company Law, the GMS conducted by electronic media can be carried out by GMS participants without being limited to space and time, of course, with the application of the cyber notary concept. Cyber notary acts to facilitate the process of validation and validity of documents and decisions made at the GMS. This research examines the use of cyber notary technology in the General Meeting of Shareholders (GMS) from a legal perspective, focusing on expediency and efficiency. Using the normative juridical legal research method, this research analyzes the laws and regulations relating to the application of cyber notary in GMS, and examines the efficiency of the application of cyber notary in GMS electronically. The results of this study show that the use of cyber notary in GMS can accelerate the decision-making process, with notaries playing an important role in ensuring the validity of the deeds produced. However, there is a conflict with the Law on Notary Position that requires the deed to be made by physically confronting the notary. Thus, the application of cyber notary in GMS can provide significant benefits for companies in simplifying the decision-making process, in accordance with the principle of legal expediency, but it is necessary to review the rules so that the application of cyber notary in GMS electronically can be applied.